Child mortality profile based on investigation of obituary records - Camila Marques Careti; Ana Helena Parra Scarpelini; Maria Cândida de Carvalho Furtado (Universidade Federal de Goias, 2014)
The present study aims at analyzing the child mortality profile Ribeirão Preto-SP inhabitants between 2009 and 2011, based on data from the Mother-Infant Mortality Committee. In this period, there were 224 deaths, of which 58 were avoidable. There were more deaths among children under a week old, with low birth weight and gestational age under 30 weeks; pre-natal care was considered insufficient in most cases. There was an association between age of death and gestational age; increased years of schooling proved to be a protective factor regarding deaths in the first week of life. The identification of real or potential risks to the child's life allows nursing professionals to plan individual and qualified assistance. Such planning allows interventions to be carried out, in the sense of improving health care and consequently children's quality of life, reducing infant mortality. doi: 10.5216/ree.v16i2.20321